2016
DOI: 10.1038/ncomms10452
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the spin Seebeck effect in compensated ferrimagnets

Abstract: Magnons are the elementary excitations of a magnetically ordered system. In ferromagnets, only a single band of low-energy magnons needs to be considered, but in ferrimagnets the situation is more complex owing to different magnetic sublattices involved. In this case, low lying optical modes exist that can affect the dynamical response. Here we show that the spin Seebeck effect (SSE) is sensitive to the complexities of the magnon spectrum. The SSE is caused by thermally excited spin dynamics that are converted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
190
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 187 publications
(212 citation statements)
references
References 29 publications
13
190
2
Order By: Relevance
“…It is possible to identify spin current generation from a system like MnF 2 since there is a large abrupt change in the spin wave spectrum through the spin-flop transition, which can be inferred from antiferromagnetic resonance experiments [42]. Both theoretical and experimental evidence for changes in the spin Seebeck effect due to changes in magnon branch degeneracy have been reported for compensated ferrimagnetic systems [8,43]. This type of change in the MnF 2 spin-flop transition could lead to a change in the net spin current and an abrupt change in the voltage response like the one observed in our devices.…”
Section: Prl 116 097204 (2016) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…It is possible to identify spin current generation from a system like MnF 2 since there is a large abrupt change in the spin wave spectrum through the spin-flop transition, which can be inferred from antiferromagnetic resonance experiments [42]. Both theoretical and experimental evidence for changes in the spin Seebeck effect due to changes in magnon branch degeneracy have been reported for compensated ferrimagnetic systems [8,43]. This type of change in the MnF 2 spin-flop transition could lead to a change in the net spin current and an abrupt change in the voltage response like the one observed in our devices.…”
Section: Prl 116 097204 (2016) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…Therefore, over the past years spin current transport has been extensively studied in paramagnetic (normal) metal (NM)/ferromagnetic insulator (FMI) hybrid structures in spin pumping, spin Seebeck effect, or spin Hall magnetoresistance (SMR) experiments. [1][2][3][4][5][6][7] In all these experiments the signal amplitude sensitively depends on the transfer of a spin current, i.e. spin angular momentum, across the NM/FMI interface and its interconversion into an electrical signal via the inverse spin Hall effect.…”
mentioning
confidence: 99%
“…[6][7] Up to now, the SSE has been investigated only for a limited number of insulating ferrimagnets. Most researches focused on garnet ferrites, like YIG, due to their ultralow damping constants (in the order of 10 -4 ) and the relative high Curie temperatures of T C ~550 K. 4,5,[8][9][10][11][12][13] Current studies on YIG have revealed that the interface effects plays an important role for the detected ISHE signals. 13 The complexity of the garnet ferrites' lattice structure makes the interface termination with adjacent detection layers complicated.…”
mentioning
confidence: 99%